2017
DOI: 10.3389/fpsyg.2017.00686
|View full text |Cite
|
Sign up to set email alerts
|

Individual Difference Variables and the Occurrence and Effectiveness of Faking Behavior in Interviews

Abstract: There is widespread fear that applicants can fake during selection interviews and that this impairs the quality of selection decisions. Several theories assume that faking occurrence is influenced by personality and attitudes, which together influence applicants’ motivation to show faking behavior. However, for faking behavior to be effective, interviewees also need certain skills and abilities. To investigate the impact of several relevant individual difference variables on faking behavior and interview succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 84 publications
(148 reference statements)
9
50
0
5
Order By: Relevance
“…Participants were then contacted by the experimenter via email with a description of the application situation (similar to Buehl & Melchers, ):
You have applied for an attractive Master's degree at a university in another city. You have received an invitation for a Skype interview [digital interview] as a preselection tool, since many people have applied for this Master's degree.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were then contacted by the experimenter via email with a description of the application situation (similar to Buehl & Melchers, ):
You have applied for an attractive Master's degree at a university in another city. You have received an invitation for a Skype interview [digital interview] as a preselection tool, since many people have applied for this Master's degree.
…”
Section: Methodsmentioning
confidence: 99%
“…In both interviews, interviewees were asked the same five interview questions (in German) which were taken from Buehl and Melchers (): (a) ‘What do you study and why did you decide to study this subject’; (b) ‘There are times when stress is very high. Can you remember a situation in which you had several deadlines at the same time; how did you handle this situation?’; (c) ‘What did you do if you did not understand complex contents of a course?’; (d) ‘Imagine you are doing a group project with four of your fellow students and you have to divide topics and tasks between each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As many interviewers accept and promote honest IM (Jansen et al., ), applicants engaging in more honest IM should receive more positive recommendations from interviews. As such, we expect that honest IM will be positively related to interviewer ratings of hirability, P–O fit, and P–J fit (H11a, 11b, and 11c), In contrast, research has found inconsistent results regarding the impact of deceptive IM on interview ratings (Buehl & Melchers, ; Levashina & Campion, ; Roulin et al., ; Swider, Barrick, Harris, & Stoverink, ). Given this, we treat the relationships between various forms of deceptive IM and interview ratings of hirability, P–O fit, and P–J fit as a research question (RQ4).…”
Section: Study 4: Preliminary Nomological Network Around Honest and Dmentioning
confidence: 99%
“…Individuals high on Honesty‐Humility value sincerity and fairness, prefer interpersonal relations to be genuine rather than based on manipulation, and are unwilling to take advantage of other individuals for personal gain (Ashton, Lee, & de Vries, ). Individuals low in Honesty‐Humility or modesty and related traits have been found to be more willing and more likely to engage in deceptive IM (Buehl & Melchers, ; Law, Bourdage, & O'Neill, ; Levashina & Campion, ). As such, we predict Honesty‐Humility to be negatively related to deceptive IM (H2).…”
Section: Study 4: Preliminary Nomological Network Around Honest and Dmentioning
confidence: 99%